Dynamic thermal imaging on actinic keratosis patients: A preliminary study. Issue 2 (25th October 2018) - Baek, Yoo Sang; Kim, Jaeyoung; Song, Jin Young; Jeon, Jiehyun; Oh, Chil Hwan
Abstract: Background: Diagnosis of actinic keratosis (AK) based only on clinical findings can be misleading, and histopathological diagnosis results in scars. Dynamic thermal imaging is a potential non‐invasive tool for the diagnosis of AK. This imaging technique quantifies the infrared (IR) radiation emitted by a subject after exposure to external thermal stimuli, such as heat or cold. Methods: Twenty‐six histopathologically confirmed AK patients participated in the study. We compared the dynamic thermal images of AK lesions and normal skin (control sites). Temperature changes were plotted as a thermal response graph. After fitting exponential curves to the thermal response graph, the curve was converted to a logarithmic form. Results: Comparison of the early thermal response graphs of lesions and control sites showed faster thermal recovery of AK lesions. There was a significant difference in the gradient component of the calculated logarithmic equation between the AK lesions and control sites ( P  < 0.001). Conclusion: Dynamic thermal imaging can be used as an auxiliary diagnostic tool for AK.